Impact of problem solving on trigonometric learning in Afro-Colombian communities - Orozco, Pedro Hurtado; Acosta, Adolfo Pimienta; Barrios, John Moreno; Pino, Alexander Leones (Frontiers in Education, 2025)
The article advocates for the need to adapt trigonometry teaching to Afro-Colombian communities through appropriate strategies that reflect their environment and culture, arguing that the use of authentic problem-solving is a relevant didactic design to foster meaningful learning, promote motivation, and strengthen students' identity. It is a qualitative, theoretical-conceptual study framed within the socio-critical paradigm and guided by the principles of Participatory Action Research (PAR). Although no fieldwork was conducted, a critical review of pedagogical, academic, and policy-related literature was carried out to support the design of a relevant educational proposal. The theoretical framework is built upon contextualized problem-solving, critical mathematics education, ethnomathematics, and PAR. It argues that teaching trigonometry through real-life problems enhances conceptual understanding, critical thinking, and the application of mathematical knowledge to everyday situations. Moreover, it highlights the potential for integrating ancestral knowledge related to navigation, topography, or Afro-Colombian craftsmanship. The results reveal both pedagogical and social advantages, as well as tensions and challenges such as misalignment with the official curriculum, gaps in teacher training, and limited resources. Nonetheless, the study also identifies opportunities to enrich teaching with culturally meaningful content. Finally, it proposes organizing participatory projects that connect teachers, students, and the community in the development of contextualized didactic materials, aiming for a more equitable, critical, and transformative mathematics education.